Probing the subtropical lowermost stratosphere and the tropical upper troposphere and tropopause layer for inorganic bromine - Werner, Bodo; Scalone, Lisa; Raecke, Rasmus; Pfeilsticker, Klaus (Atmospheric chemistry and physics, 2017)
We report measurements of CH4 (measured in situ by the Harvard University Picarro Cavity Ringdown Spectrometer (HUPCRS) and NOAA Unmanned Aircraft System Chromatograph for Atmospheric Trace Species (UCATS) instruments), O3 (measured in situ by the NOAA dual-beam ultraviolet (UV) photometer), NO2, BrO (remotely detected by spectroscopic UV-visible (UV-vis) limb observations; see the companion paper of Stutz et al., 2016), and of some key brominated source gases in whole-air samples of the Global Hawk Whole Air Sampler (GWAS) instrument within the subtropical lowermost stratosphere (LS) and the tropical upper troposphere (UT) and tropopause layer (TTL). The measurements were performed within the framework of the NASA-ATTREX (National Aeronautics and Space Administration - Airborne Tropical Tropopause Experiment) project from aboard the Global Hawk (GH) during six deployments over the eastern Pacific in early 2013. These measurements are compared with TOMCAT/SLIMCAT (Toulouse Off-line Model of Chemistry And Transport/Single Layer Isentropic Model of Chemistry And Transport) 3-D model simulations, aiming at improvements of our understanding of the bromine budget and photochemistry in the LS, UT, and TTL.Changes in local O3 (and NO2 and BrO) due to transport processes are separated from photochemical processes in intercomparisons of measured and modeled CH4 and O3. After excellent agreement is achieved among measured and simulated CH4 and O3, measured and modeled [NO2] are found to closely agree with  ≤ 15ppt in the TTL (which is the detection limit) and within a typical range of 70 to 170ppt in the subtropical LS during the daytime. Measured [BrO] ranges between 3 and 9ppt in the subtropical LS. In the TTL, [BrO] reaches 0.5±0.5ppt at the bottom (150hPa∕355K∕14km) and up to about 5ppt at the top (70hPa∕425K∕18.5km; see Fueglistaler et al., 2009 for the definition of the TTL used), in overall good agreement with the model simulations. Depending on the photochemical regime, the TOMCAT∕SLIMCAT simulations tend to slightly underpredict measured BrO for large BrO concentrations, i.e., in the upper TTL and LS. The measured BrO and modeled BrO∕Bryinorg ratio is further used to calculate inorganic bromine, Bryinorg. For the TTL (i.e., when [CH4]  ≥ 1790ppb), [Bryinorg] is found to increase from a mean of 2.63±1.04ppt for potential temperatures (θ) in the range of 350-360K to 5.11±1.57ppt for θ = 390 − 400 K, whereas in the subtropical LS (i.e., when [CH4] ≤ 1790ppb), it reaches 7.66±2.95ppt for θ in the range of 390-400K. Finally, for the eastern Pacific (170-90°W), the TOMCAT/SLIMCAT simulations indicate a net loss of ozone of −0.3ppbvday−1 at the base of the TTL (θ = 355K) and a net production of +1.8ppbvday−1 in the upper part (θ = 383K).